VD_FINDINFO HC / 2012 / 306 vom 11. Mai 2012 - VD Tribunal cantonal (2012)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, BAIL À LOYER, SOMMATION | 257d CO, 308 al. 2 CPC (CH), 319 let. a CPC (CH), 321 al. 2 CPC (CH)